Spiritual dalam Parental Discipline - Lisnawati Lisnawati (UIN Sunan Kalijaga, 2016)
Parental discipline is parent's specific strategies in applying the rules and fosters the values to their children. Mal treatmen phenomenom in child rearing, illustrated that individuals do not have a direction, which is continuosly increasing wisdom and strength of a person's wishes, in order to achieve a closer relationship with Divinity and the universe, which became one of the aspects of spirituality. this present research focused on how dynamic of parents spirituality, in child rearing practices. The result showed that spirituality was a process wich growstrough understanding and experience, so that in practice the discipline, spirituality can enhance positive parenting in practice the discipline when accompanied with the knowledge and skills in practice the discipline of parenting.